Endometriosis and infertility (Texas Journal of Medical Science, 2023)
In this article, the causes and mechanisms of infertility in endometriosis are fully explained, the four main factors of infertility related to endometriosis, the importance of the embryo factor in infertility in endometriosis, the fundamental differences in embryos.